2008
DOI: 10.1007/s10447-008-9048-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Counseling and Clinical Psychology Practitioners: Similarities and Differences on Theoretical Orientations Revisited

Abstract: The study compared the theoretical orientation preferences of practitioners of clinical and counseling psychology. A total of 221 participants (110 clinical and 111 counseling) completed a web-based survey. Theoretical orientation preference was assessed using a modified version of the Theoretical Orientation Profile Scale-Revised (TOPS-R; Worthington & Dillon in Measurement and Evaluation in Counseling and Development, 36, 95-105, 2003). MANCOVA results showed that profession, gender, and years of clinical e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 19 publications
1
9
1
Order By: Relevance
“…These findings support the view that graduate psychological training is one of the most significant determinants for the choice of CBT, but not for psychoanalysis (4). In China, medical graduates usually work in healthcare settings, including hospitals, hence, in accordance with past studies (18,19), the findings of the present study revealed that clinical psychology practitioners were prone to using CBT. A plausible explanation for this observation is that the healthcare discipline focuses on the treatment of mental disorders and that the initial models of CBT were developed to address mental disorders, including anxiety and depression (19).…”
Section: Discussionsupporting
confidence: 91%
“…These findings support the view that graduate psychological training is one of the most significant determinants for the choice of CBT, but not for psychoanalysis (4). In China, medical graduates usually work in healthcare settings, including hospitals, hence, in accordance with past studies (18,19), the findings of the present study revealed that clinical psychology practitioners were prone to using CBT. A plausible explanation for this observation is that the healthcare discipline focuses on the treatment of mental disorders and that the initial models of CBT were developed to address mental disorders, including anxiety and depression (19).…”
Section: Discussionsupporting
confidence: 91%
“…Although this study found personality as something that influenced theoretical choice, another study did not find personality as an influence (Freeman et al, 2007). Profession, gender, and years of clinical experience also influence one's theoretical approach (Ogunfowora & Drapeau, 2008).…”
Section: Graduate Students' Training and Theoretical Framework Develocontrasting
confidence: 73%
“…Additionally, in many clinical psychology graduate programs, students might align with a certain orientation because they receive a narrow view of approaches at their learning institution (Heatherington et al, 2012). For example, more clinical programs (i.e., clinical psychology) had a tendency to align with CBT (Heatherington et al, 2012;Ogunfowora & Drapeau, 2008;Poznanski & McLennan, 2003) while counseling psychology adhered to more feminist and multicultural models (Ogunfowora & Drapeau, 2008).…”
mentioning
confidence: 99%
“…The majority of students and professionals within both of these specialties recently have been found to identify themselves as eclectic, integrative, or cognitive-behavioral (Bechtoldt et al, 2001), for example, with only modest differences in relation to identification with psychoanalytic, behavioral, or humanistic orientations. The recent work of Ogunfowora and Drapeau (2008) reported no significant differences between the two specialties in relation to any of the theoretical orientations they studied, including humanistic, psychodynamic, behavioral, or biological approaches.…”
Section: Introductionmentioning
confidence: 93%
“…These historical differences are reflected in a range of contemporary distinctions between the two specialties, as well (Munley et al, 2004). Longstanding literatures have addressed the enduring distinctions between clinical and counseling psychology training programs in relation to their theoretical commitments (Norcross & Prochaska, 1982;Ogunfowora & Drapeau, 2008) and their training models (Korman, 1974;Norcross, Kohout, & Wicherski, 2005), and have sought to see whether these differences translate into differential internship placements (Brems & Johnson, 1996;Neimeyer & Keilin, 2007;Neimeyer, Rice, & Keilin, 2009;Shivy, Mazzeo, & Sullivan, 2007) or workplace experiences (Owens, Moradi, & Neimeyer, 2008).…”
Section: Introductionmentioning
confidence: 98%